PENGARUH KENAIKAN PANGKAT DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI YANG DI MEDIASI OLEH KEPUASAN KERJA PADA BADAN KEPEGAWAIAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA KABUPATEN BARITO UTARA PROVINSI KALIMANTAN TENGAH - Fie Khaeriyah (Sekolah Tinggi Ilmu Ekonomi Muara Teweh, 2025)
Salvinnia, 2023. The Effect of Promotion and Work Motivation on Employee Performance Mediated by Job Satisfaction at the Personnel and Human Resources Development Agency, East Barito Regency, Central Kalimantan Province, supervised by: This research aims to determine the effect of promotion and work motivation on employee performance which is mediated by job satisfaction at the Personnel and Human Resources Development Agency, East Barito Regency, Central Kalimantan Province. The data collection technique in this research is by distributing questionnaires to the sample, the sample used is 40 members. The data analysis technique used is Smart PLS Version 3.2.9. The research results state that promotion has a positive and significant effect on job satisfaction at the Personnel and Human Resources Development Agency of East Barito Regency, Work Motivation has a positive and significant effect on Job Satisfaction at the Personnel and Human Resources Development Agency of East Barito Regency. Promotion has a positive and significant effect on performance at the East Barito Regency Personnel and Human Resources Development Agency. Work Motivation has a positive and significant effect on performance at the East Barito Regency Personnel and Human Resources Development Agency. Job satisfaction has a positive and significant effect on performance at the East Barito Regency Personnel and Human Resources Development Agency. Job Satisfaction Mediates the effect of Promotion on performance at the Personnel and Human Resources Development Agency of East Barito Regency. Job Satisfaction Mediates the influence of Work Motivation on performance at the Personnel and Human Resources Development Agency of East Barito Regency